The effect of nanocrystalline cellulose and TEMPO-oxidized nanocellulose on the compatibility of polypropylene/cyclic natural rubber blends. (November 2022) - Mahendra, IP; Wirjosentono, B; Tamrin, T; Ismail, H; Mendez, JA; Causin, V
The effect of nanocrystalline cellulose (NCC) and nanofiber cellulose (NFC) was estimated as a means of reinforcing and compatibilizing agent of polypropylene/ cyclic natural rubber (PP/CNR) blend in terms of mechanical and thermal properties. The morphological effect of NCC and NFC on the PP/CNR blend property was determined through several characterization techniques, i.e. SEM, contact and TGA/DTG. Scanning electron microscopy (SEM) images revealed that the addition of NCC and NFC became more homogenous than without the addition of nanocellulose. The improvement of nanocomposites was also observed on the result of interphase surface tension and thermal stability. This improvement was assumed as the result of physically/ chemically interaction of nanocellulose with the backbone of PP and CNR, in which the nanocellulose can be imagined acting as a bridge to link the PP and CNR's backbone.